2022
DOI: 10.1097/j.pain.0000000000002678
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of LncRNA71132 in the spinal cord regulates hypersensitivity in a rat model of bone cancer pain

Abstract: Supplemental Digital Content is Available in the Text.LncRNA71132 works as a miRNA sponge in miR-143-5p–mediated posttranscriptional modulation of GPR85 expression in bone cancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The microRNA profiling database analysis disclosed that 45 microRNAs were significantly changed between Sham and BCP groups from 569 candidates ( Figure 2(b) ). 32 We then assessed the miR-155-5p temporal expression pattern in the spinal cord. The qPCR analysis was done to examine the variances in miR-155-5p levels in Sham and BCP groups; the miR-155-5p levels were markedly increased on day 12 post-BCP surgery in comparison with those after Sham surgery in the rat’s dorsal horn ( Figure 2(c) , *** p < 0.001 vs. Sham group; n = 4, one-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…The microRNA profiling database analysis disclosed that 45 microRNAs were significantly changed between Sham and BCP groups from 569 candidates ( Figure 2(b) ). 32 We then assessed the miR-155-5p temporal expression pattern in the spinal cord. The qPCR analysis was done to examine the variances in miR-155-5p levels in Sham and BCP groups; the miR-155-5p levels were markedly increased on day 12 post-BCP surgery in comparison with those after Sham surgery in the rat’s dorsal horn ( Figure 2(c) , *** p < 0.001 vs. Sham group; n = 4, one-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…Referring to earlier studies ( Ni et al, 2022 ), rats were thoroughly sedated with pentobarbital (50 mg/kg, i. p.) and afterwards the spinal cord was incised in 2.5-cm length using a sterile and specifically constructed PE-10 tube (Comet Bio, China), which was introduced into the expanded, subarachnoid cavity of the lumbar region. The unfixed point of the PE-10 tube was introduced into the subcutaneous tissue of the back to provide medication.…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing a multiphoton confocal microscope (Leica Microsystems, Wetzlar, Germany) photos were taken. In addition, referring to the previous references ( Shen et al, 2014 ; Xu et al, 2014 ; Ni et al, 2022 ), we performed the comparison of fluorescence intensity between different groups by averaging the fluorescence intensity for the same magnification, the same spinal cord size, and by selecting several regions that did not completely overlap.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of GPR85 by miR143 alleviates mechanical pain sensitivity in rats. [ 41 ] GPR132 SNI Male/mice 9-HODE, 13-HODE Gαq Macrophages Knockout of GPR132 diminishes SNI-induced mechanical pain sensitivity and substantially diminishes the secretion of TNFα, IL-6, and VEGF. [ 42 ] CIPN DRG GPR132 participates in CIPN by activating TRPV1 via PKC.…”
Section: Ogpcrs and Painmentioning
confidence: 99%
“…In the context of bone cancer pain (BCP), GPR85 has been demonstrated to play a vital role. In a study by Ni et al, it was found that both mRNA and protein expression of GPR85 were significantly increased in the dorsal horn of the spinal cord in a rat model of BCP and were mainly expressed on neurons [ 41 ]. Further studies showed that injection of AAV- Gpr8 5-shRNA in the dorsal horn of the spinal cord reduced mechanical pain sensitivity in rats.…”
Section: Ogpcrs and Painmentioning
confidence: 99%